The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1029/2012jd017642
|View full text |Cite
|
Sign up to set email alerts
|

Geogenic and atmospheric sources for volatile organic compounds in fumarolic emissions from Mt. Etna and Vulcano Island (Sicily, Italy)

Abstract: In this paper, fluid source(s) and processes controlling the chemical composition of volatile organic compounds (VOCs) in gas discharges from Mt. Etna and Vulcano Island (Sicily, Italy) were investigated. The main composition of the Etnean and Volcano gas emissions is produced by mixing, to various degrees, of magmatic and hydrothermal components. VOCs are dominated by alkanes, alkenes and aromatics, with minor, though significant, concentrations of O‐, S‐ and Cl(F)‐substituted compounds. The main mechanism fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 224 publications
(238 reference statements)
1
22
0
Order By: Relevance
“…In the last four decades, several studies have reported the presence of halocarbons in volcanic emissions, in most cases interpreted as related to the contribution from air contamination (Frische et al, 2006, and references therein). However, some authors (Isidorov et al, 1990(Isidorov et al, , 1992Schwandner et al, 2004Schwandner et al, , 2013Tassi et al, 2012a) reported geochemical evidences suggesting a volcanogenic source for halocarbons, especially the hydrogenated species (HCFCs), cannot be excluded. In the Solfatara fumaroles, as well as in the soil gases characterized by low air contamination (group A), CFCs and CH 3 Cl were not detected (Tables A1 and A2).…”
Section: Halocarbonsmentioning
confidence: 97%
See 1 more Smart Citation
“…In the last four decades, several studies have reported the presence of halocarbons in volcanic emissions, in most cases interpreted as related to the contribution from air contamination (Frische et al, 2006, and references therein). However, some authors (Isidorov et al, 1990(Isidorov et al, , 1992Schwandner et al, 2004Schwandner et al, , 2013Tassi et al, 2012a) reported geochemical evidences suggesting a volcanogenic source for halocarbons, especially the hydrogenated species (HCFCs), cannot be excluded. In the Solfatara fumaroles, as well as in the soil gases characterized by low air contamination (group A), CFCs and CH 3 Cl were not detected (Tables A1 and A2).…”
Section: Halocarbonsmentioning
confidence: 97%
“…This behavior may be explained admitting that these compounds can have a deep origin. Production of furans through Paal-Knorr synthesis seems to be favored at relatively high temperatures and highly acidic conditions (Tassi et al, 2010(Tassi et al, , 2012a, such as those characterizing the fluid reservoir feeding the Solfatara fumaroles. Theoretically, furans may also be produced in the soil through oxidation of organic matter induced by iron(III) and hydrogen peroxide in the presence of chloride (Huber et al, 2010).…”
Section: O-bearing Compoundsmentioning
confidence: 99%
“…Heavier hydrocarbons of thermogenic derivation are also typically present as either trace or ultra-trace species in hydrothermal environments associated with magmatic systems such as White Island (e.g., Taran and Giggenbach 2003), and Vulcano Island (Tassi et al 2012), with alkanes Fig. 3 Variability in hydrothermal and magmatic endmember components in a low temperature fumarole from White Island, New Zealand.…”
Section: 21mentioning
confidence: 99%
“…Exposure to high atmospheric concentrations of potentially harmful elements in volcanic areas is a problem that should not be neglected because many millions of people visit volcanic areas each year (Erfurt-Cooper and Cooper, 2010) and many of them get close to the volcanic vents, where the emissions are highly concentrated. Etna is one of the major destinations of worldwide volcano tourism and the tourist facilities provide access to areas close to the summit craters which are the source of huge quantities of harmful elements and compounds to the atmosphere (Aiuppa et al, 2004;Calabrese et al, 2011;Tassi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%